Sugemalimab plus chemotherapy vs. chemotherapy for metastatic non-small-cell lung cancer: A cost-effectiveness analysis - Liang, Xueyan; Chen, Xiaoyu; Li, Huijuan; Liu, Xiaoxia; Li, Yan (Frontiers in Public Health, 2023)
Background Sugemalimab is a newly developed inhibitor of programmed death ligand 1 (PD-L1). As a first-line treatment for metastatic non-small-cell lung cancer (NSCLC), sugemalimab plus chemotherapy (Sugema-Chemo) has been proven effective. Still, its cost-effectiveness has not yet been determined. The objective of this study was to assess the cost-effectiveness of Sugema-Chemo from a health care perspective in China. Methods A partitioned survival model was used. According to the GEMSTONE-302 trial, the clinical characteristics and outcomes of the patients were obtained. The outcomes were costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefits (INHB) and incremental net monetary benefits (INMB). The robustness of the model was further evaluated, as well as subgroup analyses. When the ICER was lower than the willingness to pay (WTP) threshold ($38,017/QALY or $86,376/QALY, defined as three times the per capita gross domestic product value of the general region and Beijing), the cost-effectiveness of Sugema-Chemo was assumed for general regions or Beijing. Results Compared with chemotherapy alone, Sugema-Chemo resulted in an incremental gain of 0.82 QALYs, an incremental gain of 1.26 life-years, as well as an average increase cost of $72,472. The ICER was $88,744/QALY. Model outcomes were susceptible to average body weight and cost of sugemalimab. Sugema-Chemo was cost-effective at a WTP threshold of 86,376/QALY if the average body weight was <62.44 kg or if the price of sugemalimab was <$2.996/mg. As well, Sugema-Chemo was also cost-effective when the cost of sugemalimab was <$1.839/mg for a WTP threshold of $38,017/QALY. Sugema-Chemo had a probability of > 50% being considered cost-effective in most subgroups at the $86,376/QALY threshold. However, Sugema-Chemo did not achieve cost-effectiveness (0%) in any of the subgroups when WTP was set at $38,017/QALY. Conclusion Sugema-Chemo might not be cost-effective in patients with metastatic NSCLC in China. In deciding between Sugema-Chemo and chemotherapy alone, it is essential to consider both the body weight of patients and the price of sugemalimab. A price reduction of sugemalimab under the National Healthcare Security Administration may be an effective measure to improve the cost-effectiveness of the drug.